Scoring Microbiota Function: A Proposal to Use Features of Evolutionary, Symbiotic Innovation to Recognize a “Healthy” Human Gut Microbiota - Gerald W. Tannock (Gut Microbes Reports)
Research concerning the significance of the bacterial community of the human colon (gut microbiota or microbiome) in the etiology of diseases has depended in large part on molecular and bioinformatic tools to assemble catalogs of bacterial diversity. This article proposes that the gut microbiotas of humans are collectively a metacommunity whose functions are characteristic and consistent across all healthy humans. The pathway of evolutionary innovation in the development of the symbiosis between humans and gut microbiotas is known. Therefore, it is suggested that functional scoring of these long-lasting symbiotic innovations will reap greater benefits in delineating health or disease than can comparative taxonomic analysis. Adoption of a function-scoring approach would offer opportunities for emerging researchers, worldwide, to form multidisciplinary teams to develop essential methodologies to advance this gut microbiota research.